Peru : Second Review Under the Stand-By Arrangement and Requests for Establishment of Performance Criteria Wavier of Nonobservance of Performance Criteria and Rephasing of Future Disbursements 2005 Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Peru; Second Review Under the Stand-By Arrangement and Requests for Establishment of Performance Criteria, Wavier of Nonobservance of Performance Criteria, and Rephasing of Future Disbursements-2005 Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Peru. (IMF Staff Country Reports; Country Report ;, 2007)
This paper discusses key findings of the Second Review Under the Stand-By Arrangement for Peru. The economy continued to perform well in 2004. Real GDP grew by 5.1 percent, inflation was 3.5 percent at end-December, and the fiscal deficit of the combined public sector narrowed to 1.1 percent of GDP. However, poverty remains high. The reform of the preferential public pension regime was approved in mid-December, and the authorities are making progress toward awarding transportation infrastructure in concession to the private sector.